Low success rate of stoma stapling to treat stoma prolapse and retraction - Marlene Mauseth Elveos; Kristin Bjørnland (Elsevier, 2023)
Background: Stoma prolapse and retraction are common stoma complications, and there are many available techniques for correction. Results of stoma stapling to treat prolapse/-retraction in children has not yet been reported. The aim of this study was, therefore, to present results with this technique. Methods: Retrospective study with review of medical records of patients treated with stoma stapling during 2001-2022. Results: 19 patients were identified; 12 boys (63 %). Most common underlying diagnoses were Hirschsprung's disease and anorectal malformation. There were ten colostomies and nine ileostomies. Stapling was performed under general anesthesia. The enterostomy was stapled longitudinally along the whole length of the extra-abdominal part of the stoma at three places, usually with 120° between each stapler row. A knifeless GIA stapler was used. A total of 32 stapling procedures were performed, median 1 (1-5) per patient. Median operating time was 16 (4-51) minutes, 22 % of patients needed opiates the first 24 h postoperatively, and median postoperative stay was 1 (1-4) day. There were no complications related to the stapling procedures. Success was defined as no prolapse or retraction after maximum two stapling procedures. Five (26 %) patients had successful outcome. Underlying diagnosis, type of stoma (colostomy/ileostomy) or age at stoma formation did not influence the success rate. Conclusions: Stoma stapling to treat stoma prolapse/retraction was only successful in 1/4 of patients. Although the success rate was rather low, we suggest that stoma stapling may be attempted once because it is a mini-invasive procedure. Level of evidence: IV.